Ruptura de tendones flexores profundo y superficial, y laceraciones en cara plantar y lateral del menudillo en un equino criollo colombiano. Reporte de caso (2021)
Injury to the tendons of equines is extremely common, due to the high-effort activities to which this species is subjected, on the other hand, any breed can predispose to this type of injury, the most accurate diagnosis is ultrasound, since that, through this, each anatomy structure and its abnormalities are evidenced. Thanks to this, different studies have been carried out to find out what type of treatment should be used in these cases and which is the most effective. The clinical case of a female equine, Colombian Creole, approximately 10 years old is described. On clinical examination, a laceration of the right hind limb, of approximately 6cm, was evidenced in the superficial and deep flexor tendons, with 5/5 claudication. It should be taken into account that one of the most common problems in equines is pathologies in the locomotor system, due to many factors. It is important to know that anatomically the tendons are anatomically made to support a large amount of weight and also allow the displacement of the animal with other structures. When there is an alteration in the tendons, at present, there are different types of diagnosis, and treatments, on the other hand, it must be taken into account that after injuries, they heal slowly and never regain their original biomechanical characteristics.